Abordaje práctico sobre cómo mejorar el bienestar en los bovinos - Paranhos da Costa, Mateus J. R. [UNESP]; Tarazona Morales, Ariel Marcel (Univ Antioquia, Fac Ciencias Agrarias, 2011)
Current challenges of humanity require a new paradigm for animal production, and invest time and attention to the development of new production techniques that take into account the principles of sustainability and animal welfare science. To do this, we must be committed to promoting animal welfare and health, ensure environmental sustainability, consumer satisfaction and profitability for producers. To change our relationship with animals there is no need for changes in market conditions or large investments, it is enough to know better the needs of the animals we raise, the management system adapted to its characteristics. Even in the most favorable management conditions, on farms that have technological resources and trained personnel, there is much to change, especially in the daily management of the animals. Some of the risks more evident in the traditional systems of beef production are: problems during parturition, morbidity and mortality of calves, lack of shade in the pastures, improper handling of animals, risk of injury, inadequate infrastructure, poor management practices during routine processing (marking, castration, vaccination, dehorning), poor welfare during loading, transport, unloading and slaughter. To remedy this, you can adopt good management practices, which have been shown to reduce risk and improve the welfare of cattle in different stages of the production chain. The objective of this review is to show some of the risks that reduce the welfare of cattle and examples of how the adoption of best management practices impact on improving the productivity of these production systems. Finally, some indicators for assessing welfare in production systems are shown.

Los retos actuales de la humanidad requieren establecer un nuevo paradigma para la producción animal, y dedicar tiempo y atención para el desarrollo de nuevas técnicas de producción que tengan en cuenta los principios de la sostenibilidad y la ciencia del bienestar animal. Para ello, debemos estar comprometidos con la promoción del bienestar y la salud animal, garantizar la sostenibilidad del medio ambiente, la satisfacción de los consumidores y la rentabilidad para los productores. Para cambiar nuestra relación con los animales no hay necesidad de cambios en las condiciones del mercado o de grandes inversiones, basta conocer mejor las necesidades de los animales que criamos, adaptando el sistema de manejo a sus características. Incluso en las condiciones de manejo más favorables, en las granjas que cuentan con recursos tecnológicos y personal capacitado, hay mucho que se puede cambiar, sobre todo en el manejo diario de los animales. Algunos de los riesgos más evidentes en los sistemas tradicionales de producción de ganado de carne son: problemas de las vacas durante el parto, mortalidad y morbilidad de los terneros, ausencia de sombra en los potreros, manejo inadecuado de los animales, riesgos de lesiones por infraestructura inadecuada, malas prácticas de manejo durante procesos de rutina (marcación, castración, vacunación, descorne), pobre bienestar durante el embarque, transporte, desembarque y sacrificio. Para remediar esto, se pueden adoptar buenas prácticas de manejo, que han demostrado reducir los riesgos y mejorar el bienestar de los bovinos en diferentes etapas de la cadena productiva. El objetivo de esta revisión es mostrar algunos de los riesgos que disminuyen el bienestar de los bovinos y ejemplos de cómo la adopción de las buenas prácticas de manejo repercuten sobre el mejoramiento de la productividad de estos sistemas productivos. Finalmente se muestran algunos indicadores para la evaluación del bienestar en los sistemas productivos.
Practical approach on how to improve the welfare in cattle
Keywords: Behavior; GMP; Management; risk analysis